2020
DOI: 10.3389/fpsyt.2020.514658
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Brain-Derived Neurotrophic Factor, Antioxidant Enzymes Activities, and Mitochondrial DNA in Bipolar Disorder: An Exploratory Report

Abstract: Aim: Accumulated evidence indicates that neurotrophin deregulations, oxidative stress injury, and mitochondrial dysfunction have been involved in bipolar disorder (BD); however, their real roles in BD are unclear. Investing the possible interaction between three systems is worthwhile understanding this complex process. Methods: We measured plasma brain-derived neurotrophic factor (BDNF) level, leukocytes mitochondrial DNA copy number (mtDNAcn), and activities of antioxidant enzymes in BD patients (n = 97) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…BDNF is important for the development, plasticity, and survival of neurons [75,158,159]. Six meta-analyses found decreased BDNF levels in BD patients compared with both healthy individuals and patients with unipolar depression [52, [160][161][162][163].…”
Section: Bdnfmentioning
confidence: 99%
See 1 more Smart Citation
“…BDNF is important for the development, plasticity, and survival of neurons [75,158,159]. Six meta-analyses found decreased BDNF levels in BD patients compared with both healthy individuals and patients with unipolar depression [52, [160][161][162][163].…”
Section: Bdnfmentioning
confidence: 99%
“…A similar metaanalysis consisting of 35 studies and 3798 research participants reported that BD patients exhibited lower peripheral BDNF levels compared with healthy controls [52]. Another study measured mtDNA copy number in leukocytes, plasma BDNF level, and antioxidant enzyme activity in 97 BD patients and 31 healthy controls [158]. BDNF level, mtDNA copy number, and GPX activity in the BD patients were significantly lower than those in the controls [158].…”
Section: Bdnfmentioning
confidence: 99%
“…As related above, studies in animals and humans have reported that increased oxidative damage reduced BDNF expression. However, BDNF has been shown to stimulate the expression and activities of GSH-Px and SOD; resulting in reduced oxidative damage (He and Katusic, 2012 ; Valvassori et al, 2015 ; Wang et al, 2020 ).…”
Section: Biomarkers Related To Neuroinflammation In Bipolar Disordermentioning
confidence: 99%
“…BDNF represents the most abundant neurotrophin in the brain; during the development of the central nervous system, it promotes the growth of axons and the maturation of synaptic connections, whereas in the adult brain, it plays key roles in mechanisms of maintenance, stabilization, and neuroplasticity [ 29 ]. Moreover, there is evidence showing associations between BDNF and oxidative stress markers, with increased oxidative stress damage responses coupled with decreased BDNF levels, indicating that BDNF may play a protective role against oxidative damage in neurons [ 30 ]. This neurotrophin can also be found in the peripheral blood, where it is mostly stored in platelets [ 31 ].…”
Section: Neurotrophic Systemmentioning
confidence: 99%